2009
DOI: 10.1128/jvi.00256-09
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I Subtype-Dependent Expansion of KIR3DS1 + and KIR3DL1 + NK Cells during Acute Human Immunodeficiency Virus Type 1 Infection

Abstract: ؉ and, to a lesser extent, the inhibitory receptor KIR3DL1؉ specifically expand in acute HIV-1 infection in the presence of HLA-B Bw480I, the putative HLA class I ligand for KIR3DL1/3DS1. These data demonstrate for the first time the HLA class I subtypedependent expansion of specific KIR ؉ NK cells during an acute viral infection in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
155
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(174 citation statements)
references
References 37 publications
16
155
3
Order By: Relevance
“…It was demonstrated that these KIR/HLA combinations increase the functional potential of NK cells during the ontological process of NK cell education (46,47) and that this education results in higher anti-HIV ADCC against autologous targets (48). Furthermore, an additional study (49) demonstrated that NK cells carrying KIR3DL1 are expanded in primary HIV infection. If the activation of KIR3DL1-expressing NK cells for anti-HIV ADCC occurs primarily during acute HIV infection to reduce viral load set point in SPs, it would reduce the requirement for chronic activation of this NK cell subset and explain how NK cells from SPs maintain higher functionality than do those from more rapid progressors throughout chronic infection.…”
Section: Discussionmentioning
confidence: 97%
“…It was demonstrated that these KIR/HLA combinations increase the functional potential of NK cells during the ontological process of NK cell education (46,47) and that this education results in higher anti-HIV ADCC against autologous targets (48). Furthermore, an additional study (49) demonstrated that NK cells carrying KIR3DL1 are expanded in primary HIV infection. If the activation of KIR3DL1-expressing NK cells for anti-HIV ADCC occurs primarily during acute HIV infection to reduce viral load set point in SPs, it would reduce the requirement for chronic activation of this NK cell subset and explain how NK cells from SPs maintain higher functionality than do those from more rapid progressors throughout chronic infection.…”
Section: Discussionmentioning
confidence: 97%
“…The intense cell-mediated response to HIV infection has not been demonstrated in all elite controllers suggesting that other viral control mechanisms are in effect [9,40]. Other possible mechanisms may include innate immunity mediated by natural killer cells, as evidenced by the strong association of KIR3DL1 allele in HLA B57 positive individuals [41][42][43]. Neutralizing antibodies have not been shown to have a major role, as these antibodies may be nearly absent in some elite controllers [10,44,45] and perhaps have a positive correlation with viral load as reported in studies involving LTNP [46,47].…”
Section: Controllers and Ltnpmentioning
confidence: 99%
“…Accordingly, poly I:C-stimulated DCs treated with plasma from 3 separate donors with AHIV failed to induce Th1 CD4 + T cells (as measured by IFN-γ production from the T cells), whereas poly I:C-stimulated DCs treated with uninfected donor plasma primed potent Th1 responses from naive allogeneic CD4 + T cells ( Figure 1C). NK cells expressing certain receptors have recently been shown to be associated with control of HIV infection (19), and NK cells are one of the earliest sources of IFN-γ for promoting Th1 responses (20). DCs also activate and induce IFN-γ secretion by NK cells through DC production of IL-12p70 (12).…”
Section: Introductionmentioning
confidence: 99%